2019
DOI: 10.1097/hjh.0000000000001960
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of glutathione S-transferase μ-type 1 reduces hypertension and oxidative stress in the stroke-prone spontaneously hypertensive rat

Abstract: Background: Combined congenic breeding and microarray gene expression profiling previously identified glutathione S-transferase m-type 1 (Gstm1) as a positional and functional candidate gene for blood pressure (BP) regulation in the stroke-prone spontaneously hypertensive (SHRSP) rat. Renal Gstm1 expression in SHRSP rats is significantly reduced when compared with normotensive Wistar Kyoto (WKY) rats. As Gstm1 plays an important role in the secondary defence against oxidative stress, significantly lower expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Our result is consistent with a recent study showing that transgenic overexpression of Gstm1 in the kidney injury-prone SHRSP rat rescued renal oxidative stress and HTN. 45 In the AngII-HTN model, there was no difference in SBP between WT and KO mice and we speculate that the very high dose of AngII administered potentially masked any modest BP effect of Gstm1 deletion.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our result is consistent with a recent study showing that transgenic overexpression of Gstm1 in the kidney injury-prone SHRSP rat rescued renal oxidative stress and HTN. 45 In the AngII-HTN model, there was no difference in SBP between WT and KO mice and we speculate that the very high dose of AngII administered potentially masked any modest BP effect of Gstm1 deletion.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, enzyme kinetic assays have demonstrated that GSTM1 has activity against epoxides 47 and several reactive aldehydes [48][49][50] and, in vivo, transgenic overexpression of Gstm1 in the SHRSP rat decreases renal levels of malondialdehyde. 45 The multiple substrates metabolized by GSTM1 suggest that their metabolites and downstream effects may be influenced by disease states. Identification of reactive oxygen species regulated by GSTM1 that are involved in kidney injury in these models would be informative to further elucidate the mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of the MRP1 and GST P1-1 system in NO transport and storage in tumor cells ( Figure 7 ) [ 132 , 134 , 162 , 175 ], it is of great interest that GST polymorphisms correlate with preeclampsia (high blood pressure in pregnancy), potentially because GSTs bind vasoactive NO as DNICs [ 215 ]. Furthermore, using a combination of congenic breeding and microarray gene expression profiling, Olson and colleagues have identified Gst m1 as a positional and functional candidate gene involved in blood pressure regulation [ 216 ]. This latter study also identified that transgenic SHRSP rats harboring the WKY Gst m1 gene exhibited significantly lower blood pressure and reduced oxidative stress, which are associated with hypertension and organ damage [ 216 ].…”
Section: Implications Of the Mrp1–gst Interaction For Understanding No Biology: Dnics As A Common Currency For The Storage And Transport mentioning
confidence: 99%
“…Furthermore, using a combination of congenic breeding and microarray gene expression profiling, Olson and colleagues have identified Gst m1 as a positional and functional candidate gene involved in blood pressure regulation [ 216 ]. This latter study also identified that transgenic SHRSP rats harboring the WKY Gst m1 gene exhibited significantly lower blood pressure and reduced oxidative stress, which are associated with hypertension and organ damage [ 216 ].…”
Section: Implications Of the Mrp1–gst Interaction For Understanding No Biology: Dnics As A Common Currency For The Storage And Transport mentioning
confidence: 99%
“…Its major advantage lies in their size and larger blood volume compared to mice as well as their better accessibility in contrast to larger animals [ 52 ]. The feasibility of rat model has dwindled since transgenic technologies were first pioneered in mice, but recent advances also make genetic manipulation available for rats [ 53 , 54 , 55 , 56 ]. We performed our studies in SHR (spontaneously hypertensive rat) inbred rats since they represent one of the best characterized rat models of cardiac hypertrophy [ 57 ], which is associated also with Tmem70 dysfunction in humans [ 33 ].…”
Section: Introductionmentioning
confidence: 99%